Pastoral poetry of the English Renaissance (Manchester University Press, 2021)
Renaissance pastoral poetry is gaining new interest for its distinctive imaginative vein, its varied allusive content, and the theoretical implications of the genre. This is by far the biggest ever anthology of English Renaissance pastoral poetry, with 277 pieces spanning two centuries. Spenser, Sidney, Jonson and Drayton are amply represented alongside their many contemporaries. There is a wide range of pastoral lyrics, weightier allusive pieces, and translations from classical and vernacular pastoral poetry; also, more unusually, pastoral ballads and poems set in all kinds of prose works. Each piece has been freshly edited from the original sources, with full apparatus and commentary. This book will be complemented by a second volume, to be published in 2017, which includes a book-length introduction, textual notes and analytic indices.